(3LQjeI GdGQgGH GdOhdi GdfXQjI GdYGeI dLQjeI GdGQgGH (B- (3Gge UhQgG (B- (3GdeYGdLI GdbGfhfjI decGaMJgG (B/ s - (3YHOGdMejO YHOGdNGdb Ydi GMeOs; (3eajO eMehO TgGHs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3GNP GdYfa Hjf GdGaQGO hGdLeGYGJ jJWhQ HJWhQ GdMjGI cXGgQI GLJeGYjI h GfSGfjI (B: (3hGJNPJ HYV GdLQGFe GdJbdjOjI GHYGOG LOjOI ai GTcGdgG hUhQgG h GMLGegG h GSdhH GQJcGHgG (B: (3hef gPg GdGfeGW GdGLQGejI GdLOjOI eG XgQ NdGd GdSfhGJ GdGNjQI ef LQGFe GdYfa GdJi GUHMJ LRAG ef MjGI GdfGS GdjhejI ai YGdefG GdeYGUQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2005s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B638-658s
Keywords: (3GdbGfhf GdOhdjs; (3GdGQgGH GdOhdis; (3GdLQGFe GdJbdjOjIs; (3LQGFe GdYfas; (3eHOG GdTQYjIs; (3eHOG GdGbdjejIs; (3GdOaGY GdTQYjs; (3GdGQgGH GdSjGSis; (3GdeSGgeI GdLfGFjIs; (3GdbUO GdLfGFjs; (3ehGfY GdeSFhdjIs; (3GdQcf GdOhdj dLQjeI GdGQgGHs; (3LQjeI NWa GdWGFQGJs; (3GdGNJUGU GdbVGFjs; (3GdeSFhdjI Yf GdLfGjGJ hGdLfM GdOhdjIs; (3LQjeI GNJWGa QYGjG GdOhd GdGLfHjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs